A Cross-Sectional Study to Identify the Prevalence of Obesity and Its Selected Influencing Factors among Adults Residing At Shiroli Village of Kolhapur - Mr. Shivagouda Patil; Mrs. Sheetal Kamble; Dr. Sunil Kumar Awate (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Obesity is a major public health issue worldwide and is associated with various lifestyle and dietary factors. This study was conducted to assess the prevalence of obesity and its selected influencing factors among adults residing at Shiroli village, Kolhapur. Objectives: 1. To identify prevalence of obesity among adults residing at Shiroli village. 2. To identify the factors influencing obesity among adults residing at Shiroli village. Methods: A cross-sectional study was conducted among 800 adults aged 21–45 years in PulachiShiroli village, Kolhapur district, to identify the prevalence and factors influencing obesity. The village was divided into four geographic quotas, from which 200 participants were selected using convenient sampling. Data collection tools included a structured questionnaire covering socio-demographic details, dietary habits, and physical activity, along with anthropometric measurements (height and weight) based on WHO BMI classifications. Dietary habits (10 items) and physical activity (4 items) were assessed using a 5-point Likert scale. Dependent variable: obesity prevalence; Independent variables: age, gender, religion, education, occupation, dietary habits, family income, and lifestyle factors. Adults aged 21–45 years were selected as this group is prone to obesity due to sedentary lifestyle and reduced physical activity. Results: Among the 800 participants, the majority 379 (47.4%) were aged 41–45 years, while the smallest group 47 (5.9%) belonged to 21–25 years. More than half of the respondents were female 437 (54.6%), and most were Hindus 556 (69.5%). In terms of occupation, 373 (46.6%) were housewives, and only 13 (1.6%) were engaged in government jobs. A mixed diet was reported by 594 (74.3%) participants, and 405 (50.6%) reported sleeping more than 8 hours daily. According to BMI classification, 43.3% of the participants were in the pre-obesity category, 39.8% had normal weight, 11.1% were obese (Class I and II), and 5.9% were underweight. Analysis of lifestyle and dietary factors revealed that 47.4% consumed sweetened beverages 2–3 times a month and 5% consumed daily, while 42.6% consumed sweets monthly and 5.4% daily. Nearly half of the respondents (48.5%) consumed fried foods weekly, with 6.4% consuming daily, and 20.6% regularly added sugar or honey to beverages. Intake of refined foods such as pizza or burgers was low (95.9% consumed rarely), while fruit and salad intake was moderate, with 53.1% consuming 3–4 times a week and only 8% daily. Regular intake of sprouted pulses and green vegetables was reported by 39.8%, whereas 13.8% consumed rarely. Regarding meal frequency, 42.1% ate three meals daily, while 30.9% limited intake to two meals, indicating risk of unhealthy snacking patterns. Eating out was infrequent, with 79.8% reporting less than once per month. Physical activity patterns showed that 37.1% exercised 3–4 times a week, but only 7.8% exercised daily, and yoga practice was negligible, with 84.3% never practicing. Sedentary behavior was high, with 83% spending at least 2 hours daily sitting, while sleep duration was adequate in most, as 53% reported sleeping ≥9 hours. Overall, the findings highlight that while some respondents maintained healthy habits, obesity risk factors were evident in frequent intake of high-calorie foods, inadequate fruit and vegetable consumption, limited physical activity, and high sedentary lifestyle patterns. Conclusion: Pre-obesity and obesity are highly prevalent in the studied community. Poor dietary habits, insufficient exercise, and sedentary lifestyles were major contributing factors. Targeted interventionsfocusing on lifestyle modificationhealth education and community-basedStrategies are recommended.